2017
DOI: 10.1007/s13337-017-0365-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of NADPH oxidase-2 (Nox-2) and nuclear factor-erythroid 2-related factor 2 (Nrf2) transcripts in peripheral blood mononuclear cells isolated from dengue patients

Abstract: The role of oxidative stress in the pathogenesis of dengue infection is not completely known. A recent study reveals the involvement of oxidative stress responsive molecules in the generation of host immune responses to dengue virus in vitro. Objective of the present study was to analyse the changes in the expression of oxidant-antioxidant genes Nox-2 (NADPH oxidase) and Nrf2 (nuclear factor-erythroid 2-related factor 2) in patients with dengue during the early phase of infection compared to other febrile illn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“… 63 In peripheral blood mononuclear cells from dengue patients, downregulation of Nrf2 mRNA has been observed. 64 It has been shown that Nrf2 negatively regulates PLT production through competing with NF-E2, an erythroid transcription factor. NF-E2 dominates over Nrf2 to enhance megakaryocytic maturation by promoting ROS accumulation.…”
Section: Discussionmentioning
confidence: 99%
“… 63 In peripheral blood mononuclear cells from dengue patients, downregulation of Nrf2 mRNA has been observed. 64 It has been shown that Nrf2 negatively regulates PLT production through competing with NF-E2, an erythroid transcription factor. NF-E2 dominates over Nrf2 to enhance megakaryocytic maturation by promoting ROS accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Nrf2 prevents the spread of the influenza virus infection (Ramezani et al 2018 ). Nrf2 is a major regulator during viral infections; some infections activate Nrf2, though other viral infections may provoke Nrf2 independent of the antioxidant pathway (Cherupanakkal et al 2017 ). Remarkably, Nrf2 is involved in the host immune response in patients with dengue infection (Cherupanakkal et al 2017 ).…”
Section: Nrf2 and Sars-cov-2 Infectionmentioning
confidence: 99%
“…[ 145 ] Nrf2 is a major regulator during viral infections; some infections activate Nrf2, though other viral infections may provoke Nrf2 independent of the antioxidant pathway. [ 146 ] Remarkably, Nrf2 is involved in the host immune response in patients with dengue infection. [ 146 ] According to comparison research involving 88 dengue patients and 31 patients with other febrile illnesses, dengue patients had higher levels of Nrf2 expression in their human peripheral mononuclear cells than those with other febrile illnesses.…”
Section: Nrf2 and Viral Infectionsmentioning
confidence: 99%
“…[ 146 ] Remarkably, Nrf2 is involved in the host immune response in patients with dengue infection. [ 146 ] According to comparison research involving 88 dengue patients and 31 patients with other febrile illnesses, dengue patients had higher levels of Nrf2 expression in their human peripheral mononuclear cells than those with other febrile illnesses. [ 146 ] Therefore, Nrf2 may be implicated in the virulence and pathogenesis of viral infections.…”
Section: Nrf2 and Viral Infectionsmentioning
confidence: 99%
See 1 more Smart Citation